ВПЛИВ ДЕРЖАВНОГО РЕГУЛЮВАННЯ ЕКОНОМІКИ НА СТАНОВЛЕННЯ ІНСТИТУТІВ РИНКУ (Світ фінансів, 2017)
Алексеєнко Л. М. Вплив державного регулювання економіки на становлення інститутів ринку. Розглянуто теоретичні та практичні аспекти взаємодії інститутів ринку та держави. Особливу увагу акцентовано на зростанні ролі міжнародних фінансових інституцій в координації зусиль держав щодо протидії диспропорціям економічного розвитку та розробці антикризових дій; аргументації доцільності пошуку прагматичного компромісу між ринковими системами та інституціями держави; виборі стратегічних напрямів розвитку конкурентоспроможної економіки з метою забезпечення її соціальної орієнтованості. Alekseenko L. Influence of the state administration of the economy on the institutes of the market formation. The theoretical and practical aspects of the institutes of the market and the state cooperation are reviewed. Special attention is drawn to ascending role of international financial institutions which coordinate the efforts of the states concerning the problems of counteraction (reaction) to disproportions of economic development and working out activities to prevent crises. The author of the article proves that the search of pragmatical compromise between market systems and state institutions as well as the choice of strategic development trends of competitive economics with the purpose of maintenance its social orientation are important.